Handbook on networked multipoint mulitmedia conferencing and multistream immersive telepresence using SIP : scalable distributed applications and media control over Internet - Roy, Radhika Ranjan (Boca Raton, FL : CRC Press, 2021)
Handbook on Networked Multipoint Multimedia Conferencing and Multistream Immsersive Telepresence using SIP: Scalable Distributed Applications and Media Control over Internet is the first book to put together all IETF request for comments (RFCs), and the internet drafts standards related to the multipoint conferencing and immersive telepresence. This book includes mandatory and optional texts of all standards in a chronological and systematic way almost with one-to-one integrity from the beginning to end, allowing the reader to understand all aspects of the highly complex real-time applications. It is a book that network designers, software developers, product manufacturers, implementers, interoperability testers, professionals, professors, and researchers will find to be immensely useful. Practitioners and engineers in all spectrums who are concentrating on building the real-time, scalable, interoperable multipoint applications, can use this book to make informed choices based on technical standards in the market place, on all proprietary non-scalable and non-interposable products. This book will provide focus and foundation for these decision makers.
OCLC-licensed vendor bibliographic record.
Keywords: Videoconferencing; Multimedia communications; Interactive multimedia; COMPUTERS / Computer Architecture; TECHNOLOGY / Telecommunications; COMPUTERS / Networking / Network Protocols